OB-fold Families of Genome Guardians: A Universal Theme Constructed From the Small β-barrel Building Block - Bianco, Piero R. (Frontiers in Molecular Biosciences, 2022)
The maintenance of genome stability requires the coordinated actions of multiple proteins and protein complexes, that are collectively known as genome guardians. Within this broadly defined family is a subset of proteins that contain oligonucleotide/oligosaccharide-binding folds (OB-fold). While OB-folds are widely associated with binding to single-stranded DNA this view is no longer an accurate depiction of how these domains are utilized. Instead, the core of the OB-fold is modified and adapted to facilitate binding to a variety of DNA substrates (both single- and double-stranded), phospholipids and proteins, as well as enabling catalytic function to a multi-subunit complex. The flexibility accompanied by distinctive oligomerization states and quaternary structures enables OB-fold genome guardians to maintain the integrity of the genome via a myriad of complex and dynamic interactions in both prokaryotes and eukaryotes.